IMPLEMENTASI KEBIJAKAN MANAJEMEN HIBAH PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH PROVINSI SULAWESI TENGAH - Febtiasari, Anindya (Katalogis, 2017)
This study was aims to determine the Implementation of Grants Management Policy which has been conducted by the Financial Agency and Regional Asset of Central Sulawesi Province, the informants in this study were 5 people, it consist of two Finance Agency and Regional Asset employees of Central Sulawesi Province, one councilors of Central Sulawesi and two grantees. The researcher was determinate the informants by using purposive sampling. The data were collected by using observation, interview and documentation technique. The data were analyzed by descriptive qualitative. This research shows that the implementation of the Grants Management Policy which includes Communications, Resources, disposition/attitude and bureaucratic structures were not effective yet. This study also suggested to improve the effectiveness of the implementation of grants management policy by improving the ability, the knowledge and the professionalism of the personnel resources in understanding and implementing the government policies, especially for the grants management policies, provide the technical guidance related to the management of grants to personnel resources in order to improve the competence and professionalism in order to do all of the government’s programs and policies related to the grants management policy and Standard Operating Procedure (SOP) on grant Management which has been assigned into a decision and can be used as a standard in grants management.